Micro- and Nanostructured Fibrous Composites via Electro-Fluid Dynamics: Design and Applications for Brain - Nergis Zeynep Renkler; Stefania Scialla; Teresa Russo; Ugo D'Amora; Iriczalli Cruz-Maya; Roberto De Santis; Vincenzo Guarino (MDPI AG, 2024)
The brain consists of an interconnected network of neurons tightly packed in the extracellular matrix (ECM) to form complex and heterogeneous composite tissue. According to recent biomimicry approaches that consider biological features as active components of biomaterials, designing a highly reproducible microenvironment for brain cells can represent a key tool for tissue repair and regeneration. Indeed, this is crucial to support cell growth, mitigate inflammation phenomena and provide adequate structural properties needed to support the damaged tissue, corroborating the activity of the vascular network and ultimately the functionality of neurons. In this context, electro-fluid dynamic techniques (EFDTs), i.e., electrospinning, electrospraying and related techniques, offer the opportunity to engineer a wide variety of composite substrates by integrating fibers, particles, and hydrogels at different scales-from several hundred microns down to tens of nanometers-for the generation of countless patterns of physical and biochemical cues suitable for influencing the in vitro response of coexistent brain cell populations mediated by the surrounding microenvironment. In this review, an overview of the different technological approaches-based on EFDTs-for engineering fibrous and/or particle-loaded composite substrates will be proposed. The second section of this review will primarily focus on describing current and future approaches to the use of composites for brain applications, ranging from therapeutic to diagnostic/theranostic use and from repair to regeneration, with the ultimate goal of providing insightful information to guide future research efforts toward the development of more efficient and reliable solutions.